2016
DOI: 10.1117/1.jbo.21.2.028002
|View full text |Cite
|
Sign up to set email alerts
|

Online dosimetry for temoporfin-mediated interstitial photodynamic therapy using the canine prostate as model

Abstract: Online dosimetry for temoporfin-mediated interstitial photodynamic therapy using the canine prostate as model. General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
(39 reference statements)
0
16
0
1
Order By: Relevance
“…Following I-PDT, the PSA level was higher than expected for complete treatment and it was concluded that the light dose of 5 J/cm 2 was insufficient. In a later pre-clinical study in male canines, this group suggested that the threshold light dose should be in the range of 20–30 J/cm 2 for effective I-PDT with mTHPC in the treatment of prostate cancer [ 31 ].…”
Section: Interstitial Pdt (I-pdt) In Prostate Pancreatic Head Anmentioning
confidence: 99%
“…Following I-PDT, the PSA level was higher than expected for complete treatment and it was concluded that the light dose of 5 J/cm 2 was insufficient. In a later pre-clinical study in male canines, this group suggested that the threshold light dose should be in the range of 20–30 J/cm 2 for effective I-PDT with mTHPC in the treatment of prostate cancer [ 31 ].…”
Section: Interstitial Pdt (I-pdt) In Prostate Pancreatic Head Anmentioning
confidence: 99%
“…21 For I-PDT of the prostate, multiple investigators have suggested that intratumoural light dose (i.e., light fluence, J/cm 2 ) is the key parameter to achieve an effective tumour control. 2225 To the best of our knowledge, the impact of intratumoural light irradiance (thereafter referred to as irradiance) on response and local control has not been reported for Photofrin ® -mediated I-PDT.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there could be more extensive use of multiple distributed light sources for the simultaneous illumination of different intraperitoneal surfaces, and by continuous imaging and multiple point measurements of the light distribution, with automatic feedback control to dynamically adjust the power from each light source. This type of on-line monitoring and control system has been used for other complex anatomical sites, such as whole-prostate PDT [110], guided by pre-treatment planning based on volumetric CT or MRI.…”
Section: Uneven Bowel Contoursmentioning
confidence: 99%